The Problems of Consumer Protection in Fintech Peer To Peer Lending Business Activities in Indonesia - Hari Sutra Disemadi; Mochammad Abizar Yusro; Wizna Gania Balqis (Fakultas Hukum, Universitas Warmadewa, 2020)
Industrial Revolution 4.0 has influenced the development of technology and information. The presence of financial technology (fintech) especially fintech peer to peer lending in Indonesia is proof that the Industrial Revolution 4.0 has had an influence on economic aspects as a fundamental aspect of the country. The implementation of fintech peer to peer lending in providing alternative financing to consumers is currently faced with several problems, especially issues related to consumer protection. This study uses a normative legal research method with a statutory approach. This research shows that the state has tried to provide preventive protection to consumers through several regulations, namely Bank Indonesia Regulation Number 19/12/PBI/2017 concerning the Implementation of Financial Technology that regulates the procedures for implementing fintech in Indonesia and also the OJK Regulation Number 77/POJK.01/2016 on Information Technology-Based Lending and Borrowing Services that regulates OJK's supervisory function in implementing fintech peer to peer lending in Indonesia. This protects consumers through the regulation of digital-based savings and loan providers which must be officially registered to guarantee the legality of the organizer, electronic documents by statutory provisions, and dispute resolution mechanisms in the event of a dispute related to fintech peer to peer lending business activities.